Slow electromagnetic waves in double-layer cylindrical waveguide filled with right- and left- handed media - Meshcheryakov, V. A. (Russian physics journal)
The paper presents the simulation results of the mode propagation parameters in a circular waveguide consisting of two layers of right- and left-handed materials (Veselago media). The model tests allow to conclude that there are many magnetic modes with a significant deceleration of the phase velocity.